Pentingnya Pemeriksaan Kelembaban Kulit dan Edukasi Kesehatan dalam Menangani Kulit Kering pada Lansia - Sutedja, Gina Triana; Santoso, Alexander Halim; Gunaidi, Farell Christian; Hartono, Eric; Putra, Muhammad Dzakwan Dwi (Journal of Community Service and Society Empowerment, 2025)
Hydrated skin is an important indicator of overall skin health, as water content in the stratum corneum plays a vital role in maintaining the skin’s barrier function. Inadequate hydration can lead to dry skin, increase the risk of infections, and reduce quality of life. This activity aimed to assess skin water and oil levels among the elderly population at Hana Nursing Home to help prevent dry skin. The PDCA (Plan–Do–Check–Act) approach was used, which included planning the screening activities, measuring skin water and oil levels, evaluating the results, and providing skin care education for participants with abnormal findings. A total of 36 elderly residents at Hana Nursing Home, South Tangerang, participated in this program. The results showed that 20 individuals (55.56%) had low oil levels, while 24 individuals (66.67%) had low water levels. These findings highlight the importance of maintaining skin hydration through adequate fluid intake, regular use of moisturizers, and adopting a healthy lifestyle. Early detection of skin hydration status combined with education is effective in preventing dry skin and improving the quality of life in the elderly population.